Unique Immune Gene Expression Patterns in Bronchoalveolar Lavage and Tumor Adjacent Non-Neoplastic Lung Tissue in Non-Small Cell Lung Cancer - Kuo, Chih-Hsi Scott; Liu, Chien-Ying; Pavlidis, Stelios; Lo, Yu-Lun; Wang, Yen-Wen; Chen, Chih-Hung; Ko, How-Wen; Chung, Fu-Tsai; Lin, Tin-Yu; Wang, Tsai-Yu; Lee, Kang-Yun; Guo, Yi-Ke; et al. (Frontiers in Immunology, 2018)
Background: The immune cells in the local environments surrounding non-small cell lung cancer (NSCLC) implicate the balance of pro- and anti-tumor immunity; however, their transcriptomic profiles remain poorly understood. Methods: A transcriptomic microarray study of bronchoalveolar lavage (BAL) cells harvested from tumor-bearing lung segments was performed in a discovery group. The findings were validated (1) in published microarray datasets, (2) in an independent group by RT-qPCR, and (3) in non-diseased and tumor adjacent non-neoplastic lung tissue by immunohistochemistry and in BAL cell lysates by immunoblotting. Result: The differential expression of 129 genes was identified in the discovery group. These genes revealed functional enrichment in Fc gamma receptor-dependent phagocytosis and circulating immunoglobulin complex among others. Microarray datasets analysis (n=607) showed that gene expression of BAL cells of tumor-bearing lung segment was also the unique transcriptomic profile of tumor adjacent non-neoplastic lung of early stage NSCLC and a significantly gradient increase of immunoglobulin genes’ expression for non-diseased lungs, tumor adjacent non-neoplastic lungs and tumors was identified (ANOVA, p<2x10-16). A 53-gene signature was determined with significant correlation with inhibitory checkpoint PDCD1 (r=0.59, p=0.0078) among others, where the 9 top genes including IGJ and IGKC were RT-qPCR validated with high diagnostic performance (AUC: 0.920, 95% CI: 0.831-0.985, p=2.98x10-7). Increased staining and expression of IGKC revealed by immunohistochemistry and immunoblotting in tumor adjacent non-neoplastic lung tissues (Wilcoxon signed-rank test, p<0.001) and in BAL cell lysates (p<0.01) of NSCLC, respectively, were noted. Conclusion: The BAL cells of tumor-bearing lung segments and tumor adjacent non-neoplastic lung tissues present a unique gene expression characterized by IGKC in relation to inhibitory checkpoints. Further study of humoral immune responses to NSCLC is warranted.